Protective Measures to Reduce the Risk of Pandemic Influenza from Air Travel - เมฆมาสิน, อภิชาติ (Disease Control Journal, 2008)
Protective measures to reduce the risk of pandemic influenza from air travel could minimize the effect that might arise from this travel. The measures should consist of entry screening of those coming from affected areas or the arrival of an aircraft with a possible case on board and exit screening if there was an outbreak in Thailand including medical activity and surveillance of contact cases which had to be integrated into the national preparedness plan. Preparedness in other key stakeholders with a clear contact point should be required and relevant network established and effective communication among them were essential. Communication with relevant workers, passengers and general public was also important so that they were made aware of the risks and risk-reduction measures.